(untitled) - Plato (New York, 1992)
The book discusses the nature and meaning of justice, and of the ideal state and its ruler. All subsequent European thinking about these subjects owes its character, directly or indirectly, to this most famous and most accessible of the Platonic dialogues, and the progress, development, and eventual triumph of the spirit of reason itself would be unimaginable without it
Keywords: political science - early works to 1800,utopias